2012
DOI: 10.1186/scrt144
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring mitochondrial inner membrane potential for detecting early changes in viability of bacterium-infected human bone marrow-derived mesenchymal stem cells

Abstract: IntroductionOne of the most challenging safety issues in the manufacture of cell based medicinal products is the control of microbial risk as cell-based products cannot undergo terminal sterilization. Accordingly, sensitive and reliable methods for detection of microbial contamination are called for. As mitochondrial function has been shown to correlate with the viability and functionality of human mesenchymal stem cells (hMSCs) we have studied the use of a mitochondrial inner membrane potential sensitive dye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…It is well known that proliferation of bacterial contaminants in cell cultures can be extremely efficient. In our previous study, we have shown that infection of host cell cultures with Staphylococcus and Pseudomonas species leads to at least five log increase in bacterial numbers within 24 hours [37] . On the contrary to pathogenic bacteria, proliferation of L. casei in cell culture conditions was moderate, and the number of bacteria remained at approximately 10 8 cfu/ml even during prolonged incubation (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that proliferation of bacterial contaminants in cell cultures can be extremely efficient. In our previous study, we have shown that infection of host cell cultures with Staphylococcus and Pseudomonas species leads to at least five log increase in bacterial numbers within 24 hours [37] . On the contrary to pathogenic bacteria, proliferation of L. casei in cell culture conditions was moderate, and the number of bacteria remained at approximately 10 8 cfu/ml even during prolonged incubation (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…Mitochondrion dysfunction plays an important role in cell death [44]. Mitochondria, as a key regulator of cellular processes acting as cellular oxygen sensors [45], not only produce adenosine triphosphate (ATP) but also regulate cell proliferation and death [46].…”
Section: Discussionmentioning
confidence: 99%
“…This has raised hopes of alternative stem cell therapies for the treatment of a number of degenerative conditions [14]. It was proposed that the addition of hMSCs onto allograft could restore the integrity of bone structure and enhance new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that human mesenchymal stem cells (hMSCs), most commonly derived from bone marrow, can be proliferated and differentiated into bone lineage using tissue engineering techniques [ 11 - 13 ]. This has raised hopes of alternative stem cell therapies for the treatment of a number of degenerative conditions [ 14 ]. It was proposed that the addition of hMSCs onto allograft could restore the integrity of bone structure and enhance new bone formation.…”
Section: Introductionmentioning
confidence: 99%